On the taxonomic identity and status of ’Silene sericea’ var. ’balearica’ (sect. ’Dipterosperma’, Caryophyllaceae) - Sáez Gonyalons, Llorenç; Guasp, Elisabet; Ferrer-Gallego, Pedro Pablo; López-Alvarado, Javier; Rosselló, Josep A. (Mediterranean Botany, 2019)
This paper presents a re-evaluation of the taxonomic relationships of Silene sericea var. balearica based on morphological features Critical examination of herbarium specimens (including type material) and living plants has shown that S. sericea var. balearica should be recognized at species level. Therefore, the new name, Silene migjornensis, is proposed to designate the endemic species growing on maritime sands in southern Mallorca (Balearic Islands, Spain). This taxon is described, illustrated and compared with its morphologically closest relatives from Silene sect. Dipterosperma.